XR Development with Unity A beginner's guide to creating virtual, augmented, and mixed reality experiences using Unity - Braun, Anna; Braun, Anna; Rizzo, Raffael (Packt Publishing, 2023)
Create VR, AR, and MR experiences with the help of step-by-step tutorials on VR and AR simulators, interactivity, sound and visual effects, along with advanced XR techniques such as multiplayer integrationKey FeaturesCreate impressive XR projects without the need to own expensive VR headsetsExplore Unity XR features and techniques such as hand-tracking and plane detection using the XR Interaction Toolkit and AR FoundationBring your XR projects to life with step-by-step explanations along with practical examplesPurchase of the print or Kindle book includes a free PDF eBookBook DescriptionThe drastic surge in the demand for XR development has led to an imminent need for comprehensive resources, learning material, and overall know-how in this area. This one-stop resource will ensure that professionals venturing into XR development can access all XR-related techniques to build appealing XR applications, without relying on Google every step of the way. This book is your guide to developing XR applications with Unity 2021.3 or later versions, helping you to create VR, AR, and MR experiences of increasing complexity. The chapters cover the entire XR application development process from setting up an interactive XR scene using the XR Interaction Toolkit or AR Foundation, adding physics, animations, continuous movement, teleportation, sound effects, and visual effects, to testing and deploying to VR headsets, simulators, smartphones, and tablets. Additionally, this XR book takes you on a journey from the basics of Unity and C# to advanced techniques such as building multiplayer applications and incorporating hand- and gaze-tracking capabilities. By the end of this book, you'll be fully equipped to create cutting-edge XR projects for engaging individual, academic, and industrial use cases that captivate your audience.What you will learnGet started with Unity by building your own 3D projectExplore the XR Interaction Toolkit and AR Foundation, as well as test XR applications on your PCFind out how to deploy XR projects on different platformsBuild interactive XR apps with increasing degrees of complexity by leveraging C# scriptingCreate a fully immersive VR drum scene by using Unity$1 (Bs audio and particle systemsAdd advanced XR techniques such as hand-tracking, gaze-tracking, and multiplayer capabilities to your XR appsWho this book is forThis book is for students, developers, researchers, and professionals with a background in computer science. Business analysts, PMs, and other management professionals and executives will also benefit from this book. If you have basic knowledge of programming and are looking to gain expertise in creating virtual reality and augmented reality applications in Unity, then this book is for you. While having experience as a VR game player with basic programming knowledge can enhance your understanding of the content, it is not a prerequisite.s